A Survey on Intelligent Data Analysis: Issues and Challenges - Mousami V. Munot,; Kaustubh V. Sakhare, (AG Volumes, 2022)
(IDA) that is Intelligent data analysis is a new topic that combines several disciplines, particularly AI as well as statistics, to analyse data sets automatically or semi automatically in a variety of real-world applications. All three of these areas are mutually beneficial: Several statistical procedures depend on computers, especially for big data sets, yet computational power alone cannot replace statistical expertise. There has been a rise in an intelligent data analysis system. It is goal of such a work to address a broad variety of issues that might arise when analysing data, as well as to provide solutions. A real world instance of such a risk assessment of the level crossing data is used to analyse a few of such issues and ideas.